Computer-assisted learning as an alternative to didactic lectures: a study of teaching the physics of diagnostic imaging - V.H. M. Dale; M. Sullivan; D. R. Irvine (Association for Learning Technology, 1999)
In recent years there has been an expansion in the number of undergraduate students recruited to the veterinary courses in the UK veterinary schools. This growth in student numbers has not been matched by an increase in academic staff devoted to teaching. In addition, higher education has in the 1990s suffered an approximate 20 per cent reduction in government funding if the effects of inflation and student numbers are taken into account. At the same time there has been a demand for the investigation of teaching quality, leading to the Teaching Quality Assurance process (Ellis, 1993). Thus a number of converging factors have stimulated the need to look for alternative and innovative methods of teaching in veterinary undergraduate education.